2004
DOI: 10.1074/jbc.m313634200
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Affect Diversely the Antibiotic Potency

Abstract: The effects of spermine on peptidyltransferase inhibition by an aminohexosylcytosine nucleoside, blasticidin S, and by a macrolide, spiramycin, were investigated in a model system derived from Escherichia coli, in which a peptide bond is formed between puromycin and AcPhe-tRNA bound at the P-site of poly(U)-programmed ribosomes. Kinetics revealed that blasticidin S, after a transient phase of interference with the A-site, is slowly accommodated near to the P-site so that peptide bond is still formed but with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…In agreement with previous results obtained at 6 mM Mg 2ϩ (30,33), the addition of spermine at this concentration increases the k 3 value of PTase without affecting the K s dissociation constant (Table 1). Consequently, the ratio k 3 / K s expressing the activity status of PTase is enhanced by 43%.…”
Section: Inhibition Of Acphe-puromycin Synthesis By Clindamycin-supporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with previous results obtained at 6 mM Mg 2ϩ (30,33), the addition of spermine at this concentration increases the k 3 value of PTase without affecting the K s dissociation constant (Table 1). Consequently, the ratio k 3 / K s expressing the activity status of PTase is enhanced by 43%.…”
Section: Inhibition Of Acphe-puromycin Synthesis By Clindamycin-supporting
confidence: 82%
“…In addition, its use offers many advantages to our analysis, as discussed previously (28). When adapting the photolabeling techniques to the present ionic conditions and comparing the obtained data with those already published (20,30), we found no differences in the cross-linking of ABA-spermine to 23 S rRNA (Table 2). Among the cross-links identified within the central loop of domain V of 23 S rRNA, there are two regions of ABA-spermine cross-linking of high importance, a long stretch of strong cross-links around C2452 and a second weaker site at U2506 (Fig.…”
Section: Target Moleculesupporting
confidence: 52%
See 1 more Smart Citation
“…Slow-binding enzyme inhibitors have been extensively discussed by Morrison and Walsh (35), and it has been suggested that such reactions should occur in two steps (36). In line with this, it was found that a number of macrolides, including erythromycin, bind to ribosomes in two steps.…”
Section: Table IImentioning
confidence: 54%
“…RNA folding, inhibits the binding of spiramycin, another 16-membered lactone ring macrolide (33). This prompted us to re-examine the interaction of tylosin with complex C in the presence of spermine.…”
Section: Inactivation Of Complex C By Tylosin-in Agreement Withmentioning
confidence: 99%